2015
DOI: 10.1098/rsfs.2015.0027
|View full text |Cite
|
Sign up to set email alerts
|

Crystals: animal, vegetable or mineral?

Abstract: The morphologies of biological materials, from body shapes to membranes within cells, are typically curvaceous and flexible, in contrast to the angular, facetted shapes of inorganic matter. An alternative dichotomy has it that biomolecules typically assemble into aperiodic structures in vivo, in contrast to inorganic crystals. This paper explores the evolution of our understanding of structures across the spectrum of materials, from living to inanimate, driven by those naive beliefs, with particular focus on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…They can be expected to occur in biology also as supra aggregates, nanocubic phases surrounded and protected by layers of lamellar [5,6,[62][63][64][65][66][67][68][69][70].…”
Section: Cubic Phasesmentioning
confidence: 99%
“…They can be expected to occur in biology also as supra aggregates, nanocubic phases surrounded and protected by layers of lamellar [5,6,[62][63][64][65][66][67][68][69][70].…”
Section: Cubic Phasesmentioning
confidence: 99%
“…"Worm-like", cardioid sheets and helical fossilized microstructures, among others, are thought to be the indicium of ancient type of cyanobacterial microorganisms from the Precambrian age [1,2]. The origin of life has been dated considering that these morphologies can be constructed solely by living organisms [3,4]. As it is well known, living organisms are able to fabricate biogenic minerals usually in the presence of biomolecules [5,6]; however, it has been demonstrated that complex crystalline long-range symmetry structures with similar morphologies can be synthetized under purely inorganic reactions by inducing the precipitation of carbonates or silica-carbonates in an alkaline medium [7][8][9], which resembles atmospheric conditions in an early stage of the Earth's life.…”
Section: Introductionmentioning
confidence: 99%
“…In an article with the intriguing title ‘Crystals: animal, vegetable or mineral?’, Hyde [ 3 ] explores the evolution of our understanding of biomolecules that can assemble into aperiodic structures in vivo , so enabling us to understand structures across a wide spectrum of materials, from living to inanimate, with particular focus on the development of crystallography in materials science and biology.…”
mentioning
confidence: 99%